Contribution of Assisted Inquiry Model of E-Module to Students Science Process Skill - Pratono, Ardiyana; Sumarti, Sri Susilogati; Wijayati, Nanik (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
This experimental study aims to know is there any contribution aided model of guided inquiry e-module of the science process skills of students. The experiment was conducted in SMA Institut Indonesia on 28 March to 24 April 2017. The samples are two classes using cluster random sampling technique for normally distributed populations and homogeneous. The study design used is modified comparison group pretest-posttest design. The study design used is the mean difference test, analysis of the influence between variables, and the determination of the coefficient of determination. The test results show the mean difference 5.03 t greater than t table at the 5% significance level is 1.99. Analysis of the influence between variables produce biserial coefficient value of 0.74. Calculation of the coefficient of determination shows the application of guided inquiry-aided model of e-modules accounted for 29.16% of the science process skills. Results of science process skills of observation showed that the proportion of students who achieve the experimental class was excellent and good categories was 0.51 higher than the control class is 0.25. Based on the results of this study concluded that the application of guided inquiry assisted e-module contributes to the students' science process skills.